Assessing the Effect of Visual Merchandising on the Relationship between Store Image and Mall Choice - Zainuddin, Anizah; Ridzwan, Sarah Batrisyia; Mohd, Rohani; Ridzwan, Sarah Irdina (International Journal of Engineering and Technology, 2018)
This study aims to investigate the choice of consumers in choosing to shop at a shopping mall from a visual perspective. Specifically, this study aims to examine the effect of store image and visual merchandising on consumers’ mall choices. 448 self-administered questionnaires were distributed to a major shopping mall at Damansara Utama, Selangor. LISREL software was employed to assess the validity and reliability of the constructs. Structural equation modelling was utilised on checking on confirmatory factor analyses as well as to test the hypotheses of the study. Visual merchandising was found to have a significant and direct influence on consumers’ mall choice. Store image was convincingly related to consumers’ mall choice. Results showed that store image on mall choice were mediated by visual merchandising. This paper contributes to the literature on consumers’ choice mall from the perspectives of visual. Not only is the influence of visual merchandising verified, this study also provides an overview of the motivation behind the choice of mall among consumers.